(3JMQjQ GdfTQ ef WQjb GdYTQs - (3eUWaj Hf YHO GdQMef GdGRejQj,J (B1155 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf GdEeGe GHf GdLRQj PcQ aj fTQg YOI ef cJH GdbQGAGJ Ke YRj aj HYV GdehGVY efg HYV s
(3BNQgG (B:s
(3hGeG CHhGdbGSe HcQ Hf TGPGf GdPj Qhj Yf Hf YeQ Yf ESMGb Yf Nda aj ENJjGQg aJbOe Efg Qhi Yf JSYI QLGd hbO Je HMeO Gddg Jfejb gPg GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B166 - (3U(B198s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs